Carbon Management and Hydrogen: Potential solutions for hard-to-decarbonise sectors - Bassam Fattouh; Hasan Muslemani; Martin Lambert (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2023)
The May 2021 edition of the Oxford Energy Forum covered the role of hydrogen in the energy transition in some detail,~ starting from an observation that the decarbonized energy system was expected to see an increase in the share of electricity in final consumption rising from its current 20 per cent to around 50 per cent by 2050. If anything, in the intervening 18 months, the perceived role of electricity has strengthened further, with advances in battery technology and rapid uptake of electric vehicles, such that the 2023 update to the International Energy Agency's Net Zero scenario sees the share of electricity in final consumption at 53 per cent, up slightly from the 49 per cent in the 2021 edition.~ There has been a corresponding slight reduction in the envisaged role of hydrogen, now seen to be at 8 per cent of final consumption by 2050, compared to a projection of 10 per cent previously. While such projections more than 25 years ahead are extremely uncertain, it remains clear that there will be several hard-to-abate sectors which are not suitable for electrification and where other decarbonization solutions will be required. Hydrogen remains a key technology for such sectors along with other carbon management activities, such as the deployment of carbon capture and storage (CCS) technologies, whether that be from industrial emission sources or to drive carbon removals compensating either for historic emissions or those which cannot otherwise be avoided. In January 2022, OIES published an edition of the Forum examining trends in CCS and exploring the regulatory and commercial barriers limiting the deployment of CCS at large, including regional and country experiences, and the increasing role of carbon dioxide removal (CDR) technologies in net-zero paths. In June 2022, this was followed by an issue of the Forum focused on carbon markets, evaluating global trends in compliance and voluntary market developments, including the role of complementary mechanisms such as carbon border adjustments. As part of its increasing focus on the energy transition, the Oxford Institute for Energy Studies established two additional research programmes in 2022, one on carbon management and one on hydrogen. For this edition of the Forum, it is therefore timely for these two programmes to come together to consider how carbon management and hydrogen can play a role in decarbonization of the energy system.
Keywords: 330